2013
DOI: 10.3390/nu5051672
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Dietary Fatty Acids and Inflammatory Genes on the Obese Phenotype and Serum Lipids

Abstract: Obesity, a chronic low-grade inflammatory condition is associated with the development of many comorbidities including dyslipidemia. This review examines interactions between single nucleotide polymorphisms (SNP) in the inflammatory genes tumor necrosis alpha (TNFA) and interleukin-6 (IL-6) and dietary fatty acids, and their relationship with obesity and serum lipid levels. In summary, dietary fatty acids, in particular saturated fatty acids and the omega-3 and omega-6 polyunsaturated fatty acids, impact the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(66 citation statements)
references
References 141 publications
3
62
0
1
Order By: Relevance
“…Previous studies have shown that SFAs stimulate IL-1 ␤ -induced AT infl ammation through activation of the TLR4/NF B pathway and infl ammasome complex ( 29,30 ). Recently, it has also been shown that MUFAs can attenuate IL-1 ␤ -mediated AT infl ammation through AMPK activation ( 29 ). In line with this, our results also showed a negative correlation between oleic acid and IL-1 ␤ expression in both adipose depots at baseline of the KOBS study.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Previous studies have shown that SFAs stimulate IL-1 ␤ -induced AT infl ammation through activation of the TLR4/NF B pathway and infl ammasome complex ( 29,30 ). Recently, it has also been shown that MUFAs can attenuate IL-1 ␤ -mediated AT infl ammation through AMPK activation ( 29 ). In line with this, our results also showed a negative correlation between oleic acid and IL-1 ␤ expression in both adipose depots at baseline of the KOBS study.…”
Section: Discussionsupporting
confidence: 81%
“…Decreased SCD activity is associated with increased SFA accumulation and development of infl ammation ( 15 ), and elongase (18:0/16:0) is responsible for the production of SFAs by the elongation of palmitic acid to stearic acid ( 28 ). Previous studies have shown that SFAs stimulate IL-1 ␤ -induced AT infl ammation through activation of the TLR4/NF B pathway and infl ammasome complex ( 29,30 ). Recently, it has also been shown that MUFAs can attenuate IL-1 ␤ -mediated AT infl ammation through AMPK activation ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…Взаимос-вязь генетических детерминант и пищевых факторов, опосреду-ющих хроническое воспаление жировой ткани, представлена на рис. 3 [46].…”
Section: терапевтический архив 8 2015unclassified
“…Genetic variations include SNPs that are known to influence nutrient requirements. For example, functional SNPs in the inflammatory genes TNFA, IL-1 and IL-6 have been reported to interact with dietary fatty acids to regulate the production and secretion of cytokines, predisposing an individual to inflammation and altering obesity [16,17]. Epigenetic interactions involve nutrients that can alter the structure of DNA (or of histone proteins in chromatin) so that gene expression is chronically altered.…”
Section: Gene-nutrient Interactions: Epigenetic Programmingmentioning
confidence: 99%
“…For example, Thompson et al [16] observed large allele frequency differences between African, Americans and non-African populations and distance from the equator for a variant of the CYP3A5 gene, designated CYP3A5*1/*3. The CYP3A subfamily of cytochrome P450 genes catalyzes the metabolism of endogenous substrates that include bile acids, steroids, and environmental carcinogens such as pesticides [16,17]. It was suggested that this rare variant CYP3A5*1/*3 is implicated in salt and water retention and a risk for salt-sensitive hypertension [18].…”
Section: Our Dynamic Genomementioning
confidence: 99%